A Toggle-Switch and a Feed-Forward Loop Engage in the Control of the Drosophila Retinal Determination Gene Network - Sánchez-Aragón, Máximo; Cantisán-Gómez, Julia; Luque, Carlos M.; Brás-Pereira, Catarina; Lopes, Carla S.; Lemos, M. Carmen; Casares, Fernando (Frontiers in Ecology and Evolution, 2019)
Dipterans show a striking range of eye sizes, shapes and functional specializations. Their eye is of the compound type, the most frequent eye architecture in nature. The development of this compound eye has been most studied in Drosophila melanogaster. The early development of the Drosophila eye is under the control of a gene regulatory network of transcription factors and signaling molecules called the retinal determination gene network (RDGN). Nodes in this network have been found to be involved not only in the development of different eye types in invertebrates and vertebrates, but also of other organs. Here we have analyzed the network properties in detail. First, we have generated quantitative expression profiles for a number of the key RDGN transcription factors, at a single-cell resolution. With these profiles, and applying a correlation analysis, we revisited several of the links in the RDGN. Our study uncovers a new link, that we confirm experimentally, between the transcription factors Hth/Meis1 and Optix/Six3 and indicates that, at least during the period of eye differentiation, positive feedback regulation from Eya and Dac on the Pax6 gene Ey is not operating. From this revised RDGN we derive a simplified gene network that we model mathematically. This network integrates three basic motifs: a coherent feedforward loop, a toggle-switch and a positive autoregulation which, together with the input from the Dpp/BMP2 signaling molecule, recapitulate the gene expression profiles obtained experimentally, while ensuring a robust transition from progenitor cells into retinal precursors.